Transcranial Blade Injuries and Principles of Their Safe Extraction. Issue 3 (May 2019) - Azzi, Alain J.; Saluja, Rajeet; Mankowski, Peter; Wakil, Susan; Arthurs, Bryan; Lessard, Lucie
Abstract : Abstract: Retained cranial blade injuries are uncommon events lacking standardized recommendations for appropriate surgical extraction. The authors present a case of a 30-year-old male who sustained a penetrating blade injury of the left orbit with intracranial extension through the skull base into the temporal lobe. The patient walked to the emergency room and remained alert. Clinically, the patient had only a small laceration of the left upper eyelid with no gross visual impairment. The radiological investigation confirmed the presence of a knife blade in the orbit. Intraoperative management included an intracranial approach and an extracranial craniofacial dissection for blade visualization and soft tissue protection, globe protection and to avoid any major bleeding. A thorough review of the penetrating cranial injuries literature is presented and a trauma management algorithm is offered for the care of similar injuries.